2016
DOI: 10.1002/chem.201600854
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoisomerization of Substituted Dibenzofulvene Molecular Rotors

Abstract: The synthesis, spectral and structural characterization, and photoisomerization of a family of 2-substituted dibenzofulvene molecular actuators based on (2,2,2-triphenylethylidene)fluorene (TEF) are reported. The 2-substituted species investigated are nitro (NTEF), cyano (CTEF), and iodo (ITEF). X-ray structures of these three compounds and three intermediates were determined to assign alkene configuration and investigate the effects of the 2-substituents on steric gearing. The addition-elimination reaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 108 publications
2
19
0
Order By: Relevance
“…The dibenzofulvene motors, in turn, lack a stereocenter but incorporate an axially chiral trityl moiety. Designed and synthesized by Bell and co‐workers, these systems appear promising motor candidates because their Z / E photoisomerizations around the central double bond are unidirectional and can attain high quantum yields (QYs) by appropriate substitutions (X in motor 4 ).…”
Section: Rotary Molecular Motorsmentioning
confidence: 99%
“…The dibenzofulvene motors, in turn, lack a stereocenter but incorporate an axially chiral trityl moiety. Designed and synthesized by Bell and co‐workers, these systems appear promising motor candidates because their Z / E photoisomerizations around the central double bond are unidirectional and can attain high quantum yields (QYs) by appropriate substitutions (X in motor 4 ).…”
Section: Rotary Molecular Motorsmentioning
confidence: 99%
“…7,9 In two recent studies, however, it has been demonstrated that permanent point chirality is not an absolute requirement for achieving unidirectional rotary motion by an overcrowded alkene-based motor that exhibits a chiral-like feature in the form of a pseudo-asymmetric carbon, 16 or incorporates an axially chiral trityl moiety. 17 Interestingly, unidirectional rotary motion has also been realized or conceived for systems that contain a plane of symmetry, either by exploiting mechanically interlocked architectures 18 or using polarized laser pulses 19,20 or oscillating electric fields 21 as the input energy source.…”
mentioning
confidence: 99%
“…According to previous studies, polar substituents at the 2‐position of TEF greatly increase average φ ZE / φ EZ values. They increase in the order t Bu (TTEF, 0.04), NO 2 (NTEF, 0.26), CN (CTEF, 0.39) and I (ITEF, 0.50) . The current studies add quantum yields for four additional polar substituents to this list: NH 2 (ATEF, 0.006), NMe 2 (DTEF, 0.009), NH 3 + (ATEF⋅H + , 0.20), and NMe 2 H + (DTEF⋅H + , 0.25).…”
Section: Figurementioning
confidence: 98%
“…The synthesis of ATEF was described previously and the new analog DTEF was prepared as shown in Scheme . Starting material 1 was prepared by methylation of 2‐aminofluorene with paraformaldehyde and sodium cyanoborohydride in acetic acid .…”
Section: Figurementioning
confidence: 99%